2009
DOI: 10.28945/1059
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Web-Based Instruction and Remediation Program on Student Learning

Abstract: Faculty today are challenged to meet the individualized learning needs of what is frequently a disparate student population while engaging in meaningful assessment of student learning outcomes. Learning styles and levels of preparation vary among students especially in the area of mathematics and the ability to diagnosis deficiencies and remedy needs can increase student success. Computerized homework and test management systems complete with interactive tutorials and targeted remediation exercises are being p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…These findings are consistent with the literature that reports that interactive e-book technologies support active learning as explained by the Cognitive Theory of Multimedia Learning (Bozkurt & Bozkaya, 2015;Buzzetto-More, 2015;Ciampa, 2012;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Rockinson-Szapkiw et al, 2013); save learners money (Curry, 2021;Griffiths et al, 2018); are perceived favorably (Baron et al, 2017;Wook et al, 2014); and can positively reinforce student learning and improve learner outcomes (Asrowi et al, 2019;Buzzetto-More & Ukoha, 2009;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Schwan & Riempp, 2004;Tung & Deng, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with the literature that reports that interactive e-book technologies support active learning as explained by the Cognitive Theory of Multimedia Learning (Bozkurt & Bozkaya, 2015;Buzzetto-More, 2015;Ciampa, 2012;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Rockinson-Szapkiw et al, 2013); save learners money (Curry, 2021;Griffiths et al, 2018); are perceived favorably (Baron et al, 2017;Wook et al, 2014); and can positively reinforce student learning and improve learner outcomes (Asrowi et al, 2019;Buzzetto-More & Ukoha, 2009;Y. Huang et al, 2012;Karakoç Öztürk, 2021;Schwan & Riempp, 2004;Tung & Deng, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…HBCUs have never abandoned their mission of providing educational opportunities to students who may be otherwise marginalized; however, they are currently facing a number of challenges including declining enrollment numbers and lower-than-average graduation and retention rates (Seymour & Ray, 2015). Nevertheless, HBCUs are found to provide deeply supportive educational environments that are unparalleled elsewhere with black graduates of HBCUs more likely than black graduates of other institutions to be thriving (Buzzetto-More & Mitchell, 2009;Buzzetto-More & Ukoha, 2009;Seymour & Ray, 2015). Additionally, studies have found that choosing to transfer to a Historically Black College or University over a majority serving institution is positively associated with higher GPAs, greater college persistence, and increased rates of degree completion (Umbach, Tuchmayer, Clayton, & Smith, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are 101 accredited HBCUs educating nearly 300,000 students (Buzzetto-Hollywood & Mitchell, 2019). As institutions of higher education, HBCUs are found to provide deeply supportive educational environments that are unparalleled elsewhere in the United States, with Black graduates of HBCUs more likely than Black graduates of majority serving institutions to be thriving (Buzzetto-More & Mitchell, 2009;Buzzetto-More & Ukoha, 2009;Seymour & Ray, 2015).…”
Section: Introductionmentioning
confidence: 99%